A Study on Damping Property of NiTi Elements Produced by Selective Laser‐Beam Melting. Issue 6 (3rd March 2021) - Nespoli, Adelaide; Bettini, Paolo; Villa, Elena; Sala, Giuseppe; Passaretti, Francesca; Grande, Antonio Mattia
Abstract : The damping properties of NiTi elements produced through selective laser melting are investigated by tuning the process parameters. To this end, twelve parameters' sets are selected to fabricate fully‐dense NiTi specimens. Damping is evaluated through loss factor index, mechanical loading cycles (up to 10 4 cycles), solicitation frequency and strain amplitude. Results confirm that NiTi fabricated through selective laser‐beam melting is an excellent candidate to substitute conventional materials when used in the martensite phase. Furthermore, the selected process parameters enable specific damping performances that can be collected in damping maps which turn out to be practical tools for the fabrication of NiTi parts with tunable damping response. Abstract : This article presents an overview of the dynamic damping properties of NiTi samples fabricated through selective laser‐beam melting. Results show that the printed parts have a peculiar damping response depending on the selected process parameters and higher than that registered for conventional metals.